Forged by DXZ4, FIRRE, and ICCE: How Tandem Repeats Shape the Active and Inactive X Chromosome - Bansal, Prakhar; Kondaveeti, Yuvabharath; Pinter, Stefan F. (Frontiers in Cell and Developmental Biology, 2020)
Recent efforts in mapping spatial genome organization have revealed three evocative and conserved structural features of the inactive X in female mammals. First, the chromosomal conformation of the inactive X reveals a loss of topologically associated domains (TADs) present on the active X. Second, the macrosatellite DXZ4 emerges as a singular boundary that suppresses physical interactions between two large TAD-depleted “megadomains.” Third, DXZ4 reaches across several megabases to form “superloops” with two other X-linked tandem repeats, FIRRE and ICCE, which also loop to each other. Although all three structural features are conserved across rodents and primates, deletion of mouse and human orthologs of DXZ4 and FIRRE from the inactive X have revealed limited impact on X chromosome inactivation (XCI) and escape in vitro. In contrast, loss of Xist or SMCHD1 have been shown to impair TAD erasure and gene silencing on the inactive X. In this perspective, we summarize these results in the context of new research describing disruption of X-linked tandem repeats in vivo, and discuss their possible molecular roles through the lens of evolutionary conservation and clinical genetics. As a null hypothesis, we consider whether the conservation of some structural features on the inactive X may reflect selection for X-linked tandem repeats on account of necessary cis- and trans-regulatory roles they may play on the active X, rather than the inactive X. Additional hypotheses invoking a role for X-linked tandem repeats on X reactivation, for example in the germline or totipotency, remain to be assessed in multiple developmental models spanning mammalian evolution.